Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/anie.200901999
|View full text |Cite
|
Sign up to set email alerts
|

A General Synthetic Approach to Interconnected Nanowire/Nanotube and Nanotube/Nanowire/Nanotube Heterojunctions with Branched Topology

Abstract: A large variety of interconnected nanowire/nanotube (NW/NT) and nanotube/nanowire/nanotube (NT/NW/NT, see picture) hybrid architectures with branched topology have been prepared using a combinatorial process of electrodepositing nanowires in the branched channels of anodic aluminum oxide templates, selectively etching part of the deposited nanowires, and growing nanotubes in the remaining empty channels on the ends of the nanowires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Because the nanochannels of AAO films can be either one-side open or both-side open [30,31,86], the cap structure of AAO-CNTs can be controlled with good uniformity by selecting different types of AAO templates [33,38]. [87][88][89][90][91]. Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the nanochannels of AAO films can be either one-side open or both-side open [30,31,86], the cap structure of AAO-CNTs can be controlled with good uniformity by selecting different types of AAO templates [33,38]. [87][88][89][90][91]. Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
“…Li et al [87] first synthesized well aligned Y-junction CNTs using an AAO film with Y-branched nanochannels as template. Meng et al [88,89] reported a method for preparing AAO template with a hierarchically branched structure (as shown in Figure 9). After the initial anodization to form the stem pores, the anodizing voltage was reduced by a factor of 1 n , transforming a linear pore into a multiply branched pore.…”
Section: Synthesis Of Cnts By the Aao Template Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mesh-like Au-layer was sputtered onto one surface side of the template. Then Au-NTs were electrodeposited (20 μA, 8 min) inside the AAO template in an electrolyte reported previously [17]. Next, another Au-layer was sputtered to plug up the holes of the first Au-layer, and a thick Cu-base (N 20 μm) was electrodeposited on the bottom Au-electrode to reinforce the Au-NT arrays in a previously reported electrolyte [16].…”
Section: Preparation Of Au-nt Arraysmentioning
confidence: 99%
“…CNTs provide a unique opportunity for realizing such an improvement, since they display good electrical conductivity along their tube axis and a high surface area suitable for tethering of electroactive compounds, especially those with nanoparticulate morphology. [16][17][18] Moreover, they can be synthesized by a number of different approaches and are even available in technological relevant amounts. When depositing electroactive compounds onto the surface of CNTs a number of positive effects on the electrochemical performance of such a coaxially aligned composite electrode configuration can be envisaged: (i) an improved overall electronic conductivity of the composite; (ii) a directed electrochemical accessibility combined with a high ionic conductivity as the need for additional agglomerative and conductive binder components is avoid; (iii) well directed 1D conductive pathways due to the perfect coaxial alignment of the CNTs, which enhances the Li ionic conductivity and transport within the composite; (iv) a reduced diffusion length due to the nanometric length scale of the arrays; (v) a better overall composite stability under oxidative conditions, and the structural changes experienced by the oxide during the charge/discharge cycles can be compensated for by the mechanically highly flexible CNTs.…”
Section: Introductionmentioning
confidence: 99%